TINJAUAN YURIDIS TERHADAP PUNGUTAN BIAYA PEMBUATAN SURAT TANAH SPORADIKDI DESA JUK AYAQ KECAMATAN TELEN KABUPATEN KUTAI TIMUR - Lopez, Mario (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â  The people of Juk Ayaq Village most of their livelihoods are farmers and generally have no proof of ownership of land rights, but the facts on the ground have in fact controlled the land for quite some time. Thus, for the purposes of the registration of the land in question, the public often make a letter of their own making and known by the Village Government or Village. In practice in the local community that this certificate is often called â€œsporadicâ€, but based on real conditions, in practice that the making of the letter the land that the community says as sporadic is apparently accompanied by a number of administrative fees charged by the local village or village government as they signature in the certificate, although in the provisions of the prevailing laws and regulations, there is no fee for letters the land.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  Based on the results of the research obtained can be seen that based on interviews with various parties, especially on the community / applicant aims to strength law against ownership of land can get legal certainty, so that people who initially did not recognize the legal status of the land but with the social development of the community today assumes that the status of the land must get legal guarantees under the applicable provisions, although also in practice various ways remain to be followed and obeyed.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Keywords: License Fee for Sporadic Land License